2023
DOI: 10.1126/sciadv.abq3542
|View full text |Cite
|
Sign up to set email alerts
|

From green to red: Urban heat stress drives leaf color evolution

Yuya Fukano,
Wataru Yamori,
Hayata Misu
et al.

Abstract: Prevalence of impervious surface and resulting higher temperatures in urban areas, known as urban heat islands, comprises prominent characteristics in global cities. However, it is not known whether and how urban plants adapt to such heat stress. This study focused on Oxalis corniculata , which has intraspecific polymorphism in leaf color (green and red) and examined whether the leaf color variation is associated with urban heat stress. Field observations revealed that green-leaved plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…No correlation between genetic distance and geographic distance or landscape was found for the UP and UR population pairs (Figures 3 and 4i,j , Figure S5b ), and the absence of IBD in urban herb populations is also reported by the previous studies (Fukano et al., 2023 ; Johnson et al., 2018 ; Lu et al., 2022 ). It was indicated that founder effects and population isolation in urban habitats did not significantly influence genetic differentiation in this study species.…”
Section: Discussionsupporting
confidence: 81%
“…No correlation between genetic distance and geographic distance or landscape was found for the UP and UR population pairs (Figures 3 and 4i,j , Figure S5b ), and the absence of IBD in urban herb populations is also reported by the previous studies (Fukano et al., 2023 ; Johnson et al., 2018 ; Lu et al., 2022 ). It was indicated that founder effects and population isolation in urban habitats did not significantly influence genetic differentiation in this study species.…”
Section: Discussionsupporting
confidence: 81%
“…Sweet potato leaves (SPLs) may contain anthocyanin too low for the naked eye [ 36 ], negative −a* value indicates the presence of chlorophyll, and positive values suggest the presence of anthocyanins such as pelargonidin, peonidin, and cyanidin with a purple-red-pink colour. In some genotypes that show a slightly higher colour coordinate, leaves turn slightly purple-red under heat stress [ 37 ]. Secondary metabolites, such as anthocyanins (red pigments), may play a crucial role in adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary metabolites, such as anthocyanins (red pigments), may play a crucial role in adaptation. Anthocyanins have antioxidant properties that may mitigate the damage caused by reactive oxygen species [ 37 ].…”
Section: Resultsmentioning
confidence: 99%